Sightings of Antarctic minke whales, Balaenoptera bonaerensis, near the Kiev Peninsula (West Antarctica) during the summer period of 2019 - O. Savenko (Ukrainian Antarctic Journal, 2020)
Antarctic Peninsula region is experiencing one of the fastest rates of climate change on Earth. Its waters are known as important feeding grounds for the Antarctic minke whales (Balaenoptera bonaerensis). The purpose of the present study was to reveal the summer and early autumn presence of the Antarctic minke whales in the area adjacent to the Kiev Peninsula of West Antarctica and to estimate the encounter rates of the species in the area. The boat-based photo-identification cetacean studies were initiated as part of the long-term monitoring program based at the Akademik Vernadsky station near the Kiev Peninsula of West Antarctica. From 22 January to 7 April 2019, 35 boat and yacht cruises of the 821 nautical miles of total length were conducted. There were encountered 13 Antarctic minke whales in 7 sightings. The encounter rate was 0.015 whales per nautical mile. Minke whales were encountered only in 5% of the total sightings. Three more whales were opportunistically seen from the top of Galindez Island. There were single whales sighted and small groups of up to 3 specimens (Med = 2). At least 2 individuals were identified as juveniles. Primary behavior for whales in 7 sightings was foraging, and 2 groups were observed while travelling. A total 9 individuals of the Antarctic minke whales were photo-identified during the survey, and no matches were found between the different encounters. Our pilot study indicates summer and early autumn presence of the Antarctic minke whales in the area adjacent to the Kiev Peninsula. But encounter rates seem to be low in comparison with results of some previous surveys. Our results show the possibility to monitor minke whales in the area, and further long-term complex monitoring is essential for understanding the ecology and population dynamics of the Antarctic minke whales in rapidly changing marine environment of the Antarctic Peninsula.